Association between subjective sleepiness and vigilant attention in elementary school students - Zhu, Qinye; Wada, Hiroo; Ueda, Yuito; Onuki, Keisuke; Miyakawa, Mariko; Sato, Setsuko; Kameda, Yoshihito; Matsumoto, Fumihiko; Inoshita, Ayako; Nakano, Hiroshi; Tanigawa, Takeshi (Sleep health, 2025)
Daytime sleepiness in children is a significant public health concern. This study aimed to examine the association between subjective sleepiness and vigilant attention in elementary school students, as well as the interaction effects of grade and sleepiness on this association. We enrolled 2789 students from six elementary schools in Tokyo, Japan. Sleepiness was assessed using the self-reported Karolinska Sleepiness Scale (KSS) and a parent-reported questionnaire. Vigilant attention was measured with the 3-minute brief Psychomotor Vigilance Test (PVT-B). Generalized linear models were used to examine the associations between sleepiness and PVT-B performance metrics, including response speed (mean reciprocal reaction time, 1/s) and lapse500 (number of reaction time ≥500 ms), as well as the interaction effects between sleepiness and grade. This cross-sectional study included 1955 elementary school students (aged 6-12 years; 52% boys). Significant interactions between KSS and grade were observed for response speed (B = −0.0032, FDR-adjusted q < 0.05) and lapse500 (B = 0.0096, FDR-adjusted q < 0.01). Similarly, significant interactions between parent-reported sleepiness (“falling asleep during an activity”) and grade were found for lapse500 (B = 0.0347, FDR-adjusted q < 0.05). Our findings indicate that the association between sleepiness and vigilant attention among children varies by age, emphasizing the importance of considering developmental differences when evaluating sleep health in pediatric populations.